Tuberculosis Challenging Pathognomicity of Atraumatic Avulsion of the Lesser Trochanter for Malignancy: A Rare Case Report. Issue 3 (18th July 2022) - Sharma, Amit; Kamboj, Kulbhushan; Kumar, Roshan; Sud, Alok
Abstract : Case: A 40-year-old man presented with spontaneous, atraumatic right groin pain and inability to bear weight secondary to an isolated avulsion of the right lesser trochanter. Magnetic resonance imaging of the affected hip was suggestive of an infection, and a computed tomography–guided biopsy was remarkable for Mycobacterium tuberculosis, which was successfully managed with antitubercular therapy and activity modification. Conclusion: Although an isolated spontaneous avulsion of the lesser trochanter is typically pathognomonic for malignancy, an infectious etiology, such as tuberculosis, should also be considered in the differential diagnosis.